Pengaruh Komite Audit, Company Size dan Leverage terhadap Kecurangan dalam Laporan Keuangan - Azizah, Dyana Nur; Taqwa, Salma (Universitas Negeri Padang, 2025)
This study seeks to offer a refined perspective in examining the influence of the audit committee, corporate scale, and leverage on the occurrence of financial reporting fraud among manufacturing entities listed on the Indonesia Stock Exchange (IDX) throughout the 2021–2023 timeframe. Fraudulent behavior in financial statement preparation is considered a critical issue, as it undermines investor trust and poses risks to various stakeholders. A quantitative approach is adopted, applying an associative research design. The data employed in this research are secondary in nature, obtained from the annual financial disclosures of the firms under study. The analysis is conducted using logistic regression. The results indicate that (1) the audit committee has no statistically meaningful effect on financial reporting fraud, (2) firm size is inversely and significantly associated with the likelihood of fraudulent reporting, and (3) leverage does not exert a significant influence. These insights highlight that firm size may serve as a deterrent to fraud, whereas audit committees and leverage require further reinforcement in function and oversight to effectively minimize the risk of misreporting.